ANALISA IMPLEMENTASI SISTEM PENGADUAN LAYANAN PELANGGAN INIDHOME PADA WITEL MEDAN - Muhammad Ridho; Arpan (Jurnal Nasional Teknologi Komputer, 2025)
This study discusses the implementation of QR Code service as a customer complaint system on Indihome, a flagship product of PT Telkom Indonesia. This service aims to simplify the process for customers to report internet issues without needing to contact the call center or visit the office. By scanning the QR Code, customers can easily fill out a complaint form that is directly linked to repair technicians. The results show that the QR Code service enhances efficiency and responsiveness in handling customer complaints, as well as providing convenience for users who no longer face the burden of call charges. However, challenges remain for long-term customers who are less familiar with this technology. This study also highlights the importance of effective socialization to both staff and customers to ensure the service is fully utilized in the future.